Putting CAOS to the test: using cards as an ideation tool for proposing creative classes - Zimermann, Priscila; Padovani, Stephania (InfoDesign, 2025)
This article focused on tests reports conducted by elementary and high school teachers on a tool designed to help them developing classes that encourage creative thinking in students. It is a set of 32 cards, called CAOS, based on ideation techniques commonly used in Design and related fields. The research is characterized as qualitative and applied. Data collection was carried out through workshops held in educational institutions. As a result, we found the use of the cards promising and identified four different ways of using them to structure and propose creative classes.